(untitled) (Global Journal of Human-Social Science, 2017)
Micro and Small Enterprises (MSEs) promotion and job creation go hand in hand in poverty reduction. Product diversification among MSE sis known to contribute to risk mitigation and stable MSE sector for job creation across the world. This study investigated determinants of product diversification among MSEs in Wolaita Zone, Ethiopia. Multi-stage sampling technique was employed to select 352 enterprises by using Yamane (1967) formula with 5 per cent precision and 95 per cent confident level. Data were collected using interview schedule through face-to-face interview, observation, key informant interview and focus group discussion and data analyses were carried out by using descriptive, inferential statistics and econometric model. Econometrics result indicated that ten variables significantly determined the probability of product diversification decision.